Dampak Influencer Marketing dan FOMO terhadap Pembelian Impulsif Produk Fashion di TikTok - Michelle Ratu Syalsabila; Dias Regian Pinkan (Prodi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik USB YPKP, 2026)
The purpose of this study is to understand and analyze the influence of Influencer Marketing and Fear of Missing Out (FoMO) on the behavior of Impulsive Buying of fashion products on TikTok among students of the Communication Studies Study Program at 'Aisyiyah University Yogyakarta. This study uses a quantitative approach with multiple linear regression analysis techniques. The research population amounted to 292 students of the Class of 2022-2025 who, with a sample of 100 respondents were determined through purposive sampling techniques. Data collection using a google form questionnaire. The results showed that influencer marketing had no significant effect on impulsive buying (B=-0.048; t=-0.678; sig.=0.499>0.05), while FoMO had a positive and significant effect (B=0.580; T=8.370; sig.<0.001). The regression model was simultaneously declared feasible (F=38.949; sig.<0.001), and was able to explain 43.4% of the impulsive buying variation (Adjusted R2=0.434), while the remaining 56.6% were explained by factors other than the model. These findings indicate that FoMO has a stronger role than influencer marketing in encouraging impulsive buying, in line with the Stimulus-Organism-Response framework which emphasizes the role of individual internal processes in generating behaviors.